(untitled) (Eurasian Journal of Ecology, 2018)
Today, the Internet network, Wi-Fi, mobile phones, which are the main sources of electromagnetic fields have become an integral part of everyone’s life. The electromagnetic field of the environment, the field is not visible, but to some extent, have a negative impact on the human body. Especially great is the negative impact on the nervous system, which causes the deterioration of thinking ability of human memory function. Today in many frms, higher education institutions, in schools, in homes installed Wi-Fi network. It is proved that an excessive load is a function of the result of close scrutinizing the screen leads to diseases of the eye. The study of eye diseases, their influence on other bodies has recently become an important issue. To work were taken healthy students aged 20-21 years. They were divided into two groups according to differences in the functions of: in the first group were students with normal function of, and in the second group suffering from myopia performance features of -3 to -5. For the study were used temperature behavior of biologically active points of the standard meridian, symmetrically arranged on the surface of the skin of the right and left side of the man. Registration temperature readings were made with a «Biotemp-2» device. Key words: biological hotspots, biophysical indicators, electromagnetic field, meridian, myopia, temperature, wi-fi, еnvironment.